THE USE OF GOOGLE CLASSROOM AS AN ONLINE LEARNING MEDIA FOR ENGLISH ENGINEERING - eka resty novieta sari (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2022)
The COVID-19 pandemic has indirectly pushed lecturers out of their comfort zone from conventional teaching to distance teaching (online). This study uses Google Classroom as a medium in distance learning for English courses because this media can connect lecturers with students online. This is a qualitative study that the author is conducting in order to have a better understanding of distant learning in order to reduce the spread of covid-19 on campus. Students enrolled in Informatics Engineering class 2B were the subjects of this study. The survey's findings were broken down into three categories: student perspectives on the success of studying with Google Classroom, the simplicity of using Google Classroom, and the obstacles found during online lectures. According to the findings of the study, the implementation of Google Classroom is considered successful since it can make it easier to complete lecture assignments, improve the learning effectiveness, and assist students in learning. Furthermore, in terms of usability, Google Classroom is simple to learn, comprehend, utilize, and adapt. In addition, there are limitations to utilizing Google Classroom, such as quotas and internet access.